2010
DOI: 10.1002/jsfa.4034
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of lactic acid bacteria from jiang-sun (fermented bamboo shoots), a traditional fermented food in Taiwan

Abstract: Results suggest that L. plantarum is the main LAB present during the fermentation of jiang-sun. To our knowledge, this is the first report describing the distribution and varieties of LAB that exist in the jiang-sun fermentation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Growth of LAB decreased from 6 th day onwards for both the batches. Similar LAB growth was also observed in other studies on lactic acid fermentation on different products (Tamang and Sarkar, 1996;Sánchez et al, 2000;Chen et al, 2010). Salmonella and shigella were detected in fresh bamboo shoots at 4.49 log cfu/mL, which was totally inhibited by 8 th day of fermentation in both the batches.…”
Section: Change In Reducing Sugars Content Reducing Sugars Likesupporting
confidence: 87%
See 1 more Smart Citation
“…Growth of LAB decreased from 6 th day onwards for both the batches. Similar LAB growth was also observed in other studies on lactic acid fermentation on different products (Tamang and Sarkar, 1996;Sánchez et al, 2000;Chen et al, 2010). Salmonella and shigella were detected in fresh bamboo shoots at 4.49 log cfu/mL, which was totally inhibited by 8 th day of fermentation in both the batches.…”
Section: Change In Reducing Sugars Content Reducing Sugars Likesupporting
confidence: 87%
“…Above results are comparable with pH of some fermented bamboo shoot products of North East India like mesu, soidon, soibum, soijim, ekung, eup and hirring having average pH of 3.9, 4.2, 4.2, 4.1, 3.9, 4.1 and 4.0 respectively (Tamang et al, 2008;Tamang and Tamang, 2009). During the manufacturing of jiang-sun (fermented bamboo shoots product of Taiwan), a pH of 4.2 was also observed in the day-1 fermented sample, and a pH of 3.5 was observed in the 30-day sample (Chen et al, 2010). Medoua et al (2008) reported that, during first two days of natural fermentation of yam (Dioscorea dumetorum) hardened tubers, pH decreased from 5.5 to 4.8 and then to 3.9 after 14 days of fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Chinese steamed buns, sour mifen, Mongolia traditional dairy product, fermented vegetable juice, pickles, fu-tsai, Cantonese sausage, koumiss, chigee, jiaoke, fermented meat product, jiang-sun, sour milk Luangsakul, Keeratipibul, Jindamorakot, & Tanasupawat, 2009;Lu, Peng, Cao, Tatsumi, & Li, 2008;Ji, Fang, Wei, Zhang, & Menghebilige, 2008;Zhao, Quan, Li, An, & Cui, 2008;Xiong, Wang, Lu, & Xiong, 2004;Wu & Zou, 2007;Li, Wang, Zhang, & Bai, 2008;Jiang, Li, Zhang, & Ren, 2008;Zhao, Huang, Fan, & Luo, 2002;Yang, Ji, Li, & He, 2005;Wang et al, 2008;Liu, Du, & Huo, 2008;Chao et al, 2009;Lv & Zhang, 2004;Wu et al, 2009;Uchida et al, 2007;Sun, Wang, Zhang, Menghe, & Zhang, 2007;An, Adachi, & Ogawa, 2004;Gong, Meng, & Wang, 2010;Xu et al, 2008;Chen, Wu et al, 2010;Zhao & Huo, 2008 Lactobacillus pentosus Chinese steamed buns, fermented meat product, Mongolia traditional dairy product, koumiss, chigee, Xuanwei ham Luangsakul et al, 2009;Liu, Ao, Li, & Zhan, 2007;Guo, Wang, Du, Zhao, & Huo, 2006;An et al, 2004;Liu, Lv, et al, 2008 Lactobacillus paraplantarum Chinese steamed buns Luangsakul et al, 2009 Lactobacillus casei Chinese steamed buns, Mungbean starch,…”
Section: Lactobacillus Plantarummentioning
confidence: 99%
“…lactis Stinky tofu, Mongolia traditional dairy product, Taiwanese fermented ham, jiang-sun, sour milkChao et al, 2008;Ji et al, 2008;Guo et al, 2006;Tu et al, 2010;Chen, Wu, et al, 2010;Zhao, & Huo, 2008 Lactococcus lactis sp. cremoris Stinky tofu, chigee, Taiwanese fermented hamChao et al, 2008;An et al, 2004; Tu et al, 2010 Lactococcus raffinolactis Mongolia traditional dairy productJi et al, 2008 Lactococcus garvieae Mongolia traditional dairy product, Taiwanese fermented hamGuo et al, 2006; Tu et al, 2010 Leuconostoc carnosum Stinky tofu, Taiwanese fermented hamChao et al, 2008; Tu et al, 2010 Leuconostoc citreum Stinky tofu, fu-tsai, Taiwanese fermented hamChao et al, 2008;Chao et al, 2009;Tu et al, 2010 …”
mentioning
confidence: 99%
“…Diversity of LAB in various Taiwanese fermented foods, such as fermented cummingcordia ( pobuzihi ), fermented cucumbers ( jiang‐gua ), fermented ginger ( yan‐jiang ), fermented bamboo shoots ( jiang‐sun ), fermented mustard ( suan‐tsai ) and fermented wax gourd ( yan‐dong‐gua ), has been previously studied in our laboratory (Chen et al . , , , ; Lan et al . ; Chang et al .…”
Section: Introductionmentioning
confidence: 99%